The determinants of share price volatility among public listed local banks in Malaysia/ Syairah Aimi Zulkifli - Zulkifli, Syairah Aimi (Faculty of Business and Management, 2011)
The market volatility always excites the industry resulting from the investors’ interest in maximizing their returns. The recent natural tragedy in Japan and geopolitical crisis in Middle East countries also affect the share trading behavior. This will create the uncertainties in the share prices as explained by the random walk hypothesis that support the efficient market hypothesis. Amongst the sectors that directly affected is the financial institution. The macroeconomic factors such as financial crisis, inflationary rate and trade imbalance will influence the banking industry share prices. As a result, this study aims to examine the determinants of share price volatility among public listed local banks in Malaysia. The researcher focuses on those banks that are listed in OSK 188 (under OSK Securities Berhad). The determinants include earnings per share (EPS), net asset, net cash flow and dividend. All these factors are independent variables towards share price volatility, the dependent variable, to determine the relationship for each variable. This research uses the data from year 2006 until 2009 on a quarterly basis for seven selected public listed local banks in Malaysia. The Generalized Least Square (GLS) panel data analysis used in this study shows the net cash flow is the strong explanatory powers towards the share price volatility.